Reanalysis of Ωc→Ξc+K- Decay in QCD - T. M. Aliev; S. Bilmis; M. Savci (Advances in High Energy Physics)
The strong coupling constants of newly observed Ωc0 baryons with spins J=1/2 and J=3/2 decaying into Ξc+K- are estimated within light cone QCD sum rules. The calculations are performed within two different scenarios on quantum numbers of Ωc baryons: (a) all newly observed Ωc baryons are negative parity baryons; that is, the Ωc(3000), Ωc(3050), Ωc(3066), and Ωc(3090) have quantum numbers JP=1/2- and JP=3/2- states, respectively; (b) the states Ωc(3000) and Ωc(3050) have quantum numbers JP=1/2- and JP=1/2+, while the states Ωc(3066) and Ωc(3090) have the quantum numbers JP=3/2- and JP=3/2+, respectively. By using the obtained results on the coupling constants, we calculate the decay widths of the corresponding decay. The results on decay widths are compared with the experimental data of LHC Collaboration. We found out that the predictions on decay widths within these scenarios are considerably different from the experimental data; that is, both considered scenarios are ruled out.